EFFECT OF ETHANOLIC NEEM (Azadirachta indica) LEAVES EXTRACT ON DEVELOPMENT OF SPERMATID AND ANDROGEN RECEPTOR EXPRESSION IN THE TESTIS OF RABBIT - Usma Aulia; Sri Wahyuni; Gholib Gholib; Dasrul Dasrul; Mulyadi Adam; Erdiansyah Rahmi; Abdullah Hamzah (Universitas Syiah Kuala, 2023)
The objective of this study was to determine the effect of ethanol extract of neem (Azadirachta indica) leaves on the number of spermatids and androgen receptor expression in the testicular tissue of New Zealand White (NZW) rabbits. Twelve adults male NZW rabbits with body weight (BW) 2-2.5 kg were divided into three treatment groups (n = 4), namely P1 (control group) given 0 mg/kg BW, P2 and P3 were given 200 mg/kg BW and 300 mg/kg BW of neem leaves ethanol extract respectively. The extract was administered orally using a gastric tube for 52 days. At the end of the treatment, the rabbits were terminated and the testes were collected to be processed into histological preparations and stained with Periodic Acid Schiff (PAS) staining to detect the number of spermatid and Immunohistochemical (IHC) staining to detect androgen receptor expression. The results showed that neem leaves extract administered at P3 rabbits significantly decreased the number of spermatids and androgen receptor expression in myoid peritubular cells and connective tissue P0.05), but not significantly different in the Leydig cells and blood vessels (P0.05) of testicular tissue. The conclusion of this study is that the ethanol extract of neem leaves at a dose of 300 mg/kg BW can be used as a contraceptive candidate compared to a dose of 200 mg/kg BW.